PROMIS(®) Pediatric Self Report Scales Distinguish Subgroups of Children Within and Across Six Common Pediatric Chronic Health Conditions - DeWalt, Darren A. (Qual Life Res, 2015)
PURPOSE: To conduct a comparative analysis of eight pediatric self-report scales for ages 8-17 years from the National Institutes of Health (NIH) Patient Reported Outcomes Measurement Information System (PROMIS(®)) in six pediatric chronic health conditions, using indicators of disease severity. METHODS: Pediatric patients (N = 1,454) with asthma, cancer, chronic kidney disease, obesity, rheumatic disease, and sickle cell disease completed items from the PROMIS pediatric mobility, upper extremity functioning, depressive symptoms, anxiety, anger, peer relationships, pain interference, and fatigue self-report scales. Comparisons within the six pediatric chronic health conditions were conducted by examining differences in groups based on disease severity using markers of severity that were specific to characteristics of each disease. A comparison was also made across diseases between children who had been recently hospitalized and those who had not. RESULTS: In general, there were differences in self-reported health outcomes within each chronic health condition, with patients who had higher disease severity showing worse outcomes. Across health conditions, when children with recent hospitalizations were compared with those who had not been hospitalized in the past six months, we found significant differences in the expected directions for all PROMIS domains, except anger. CONCLUSIONS: PROMIS measures discriminate between different clinically meaningful subgroups within several chronic illnesses. Further research is needed to determine the responsiveness of the PROMIS pediatric scales to change over time.